an ANALYSIS OF METAPHOR IN “ A FAMILY AFFAIR” BY KATE CHOPIN - Ria Monika (Journal of English Education, Literature and Linguistics, 2020)
This researchs analyzed the types of metaphor and the meaning of metaphor in Kate Chopin’s story “ A Family Affair”. Metaphor is part of figurative language that compares one thing to another. According to Lakoff and Johnson (1980) in the classical view, metaphor can be defined as a figure of speech or trope in which a comparison is made between two unlike things that share certain characteristics.The aim of this research is to get clear descriptions of the types of metaphor find in this short story and to implied the meaning of each metaphor in Kate Chopin’s story “ A Family Affair”. Descriptive qualitative research method was used in conducting the research. The techniques of qualitative method is used to collect and identify the data.The results of this research were found nine metaphors in Kate Chopin’s story “ A Family Affair”. The types of metaphor that found in this research are ontological metaphorand conceptual metaphor. The types of metaphor that often found in this research conceptual metaphor. The meaning of each metaphor is different depends on the types that use in the short story.In conclusion, Kate Chopin’s story “ A Family Affair” has so many metaphors that should be analyzed. The types and the meaning of each metaphor that found in this researches based on the Lakof & Jhonson (1980) theory that lift the metaphor clearly.